USO DA RADIAÇÃO SOLAR NA DESINFECÇÃO DA ÁGUA DE POÇOS RASOS* - Amaral, L.a. [UNESP]; Nunes, A.p. [UNESP]; Castania, J. [UNESP]; Lorenzon, C.s. [UNESP]; Barros, L.s.s. [UNESP]; Nader, A. [UNESP] (Instituto Biológico, 2022)
This study evaluated the effictiveness of expusure to solar radiation for disinfecting water samples from shallow wells. Water sample were placed into 2-liter PET (Polyethylene Terephthalate) exposed to sun rays for 2, 5 and 12 hours. Probably numbers of total coliform bacteria, Escherichia coli and mesophyl microorganisms were determined before and after exposure to sun and in samples protected from the sun (controls) for 2, 5 and 12 hours. Bacterial re-growth after a 72h-exposure to the sun in samples which were protected from the sun rays and the amount of energy received by the samples after the three exposure periods to sun radiation were also evaluated. Results showed that sun radiation was effective for water disinfection with 98.2%, 99.9% and 100% reductions in mesophyl microorganisms, total coliform bacteria and E. coli respectively after a 12h-exposure to sun rays. Lack of re-growth of all microorganisms analyzed after a 12h exposure to sun rays was confirmed. Results showed that exposure of water placed in PET bottles for human consumption may be used to diminish water-transmitted disease risks.

Com o objetivo de avaliar a eficiência da exposição à radiação solar na desinfecção da água, amostras de água de poços rasos foram acondicionadas em garrafas PET (Polietileno Teraftalato) com volume de 2.000 mL, e expostas ao sol por 2, 5 e 12h. Antes da exposição, após a exposição e em amostras que permaneceram 2, 5 e 12h protegidas do sol (controles) foram determinados os números mais prováveis de coliformes totais e Escherichia coli e os números de microrganismos mesófilos. Foi verificado ainda o recrescimento bacteriano após 72h da exposição ao sol em amostras protegidas da ação da luz solar e a quantidade de energia recebida pelas amostras após os três tempos de exposição à radiação solar. Os resultados obtidos evidenciaram que a radiação solar foi eficaz na desinfecção da água com reduções, após 12h de exposição, de 98,2%, 99,9% e 100% nos números de microrganismos mesófilos, coliformes totais e E. coli, respectivamente. Foi verificada a ausência de recrescimento de todos microrganismos pesquisados após 12h de exposição ao sol. Os resultados evidenciaram que a exposição à radiação solar da água de consumo humano, acondicionada em garrafas PET, pode ser utilizada para diminuir o risco de enfermidades de veiculação hídrica.
SOLAR RADIATION IN THE DISINFECTION OF SHALLOW WELL WATER
Keywords: Solar radiation; water quality; disinfection; Escherichia coli; Radiação solar; qualidade de água; desinfecção; Escherichia coli